(untitled) (UTM Press - Edited Book, 2025)
Understanding construction contracts requires more than theoretical knowledge where it demands engagement with the intricacies of real-world scenarios. This book chapter bridges the gap between academic principles and practical application through an innovative case study methodology, designed to resonate with both professionals and students in the construction field. Within these pages lies a carefully curated collection of hypothetical case studies, inspired by recurring challenges in construction management. Each case study has been thoughtfully crafted to explore key contractual provisions and their implications in construction projects. From dissecting complex issues to simulating real-world scenarios, the book empowers readers to navigate contractual intricacies with clarity and confidence. The book serves as both a teaching resource and a learning guide, offering educators versatile tools to facilitate dynamic classroom discussions. Simultaneously, it provides students with practical insights, encouraging critical thinking and problem-solving skills vital for addressing contractual challenges. Whether you are an academic seeking innovative pedagogical tools or a practitioner aiming to deepen your understanding, this book chapter delivers a rich blend of theory and practice. Dive in to unravel the complexities of construction contracts and cultivate the skills essential for success in the construction industry.